Mechanical Properties, Oil and Ozone Resistance of EPDM/NBR Blends Filled with Hybrid Fillers for Fuel Tank Rubber-Cover Applications - Prasertsri, Sarawut; Saehan , Ekachai; Nuinu, Pranee (Burapha Science Journal, 2026)
This research aimed to investigate the optimal blend ratio of ethylene propylene diene rubber (EPDM) and acrylonitrile butadiene rubber (NBR) filled with hybrid fillers, including carbon black and calcium carbonate at 100 parts per hundred parts of rubber (phr) for fuel tank rubber-cover applications. The varied ratios of EPDM/NBR were 100/0, 70/30, 50/50, 30/70 and 0/100 %wt/wt. For mixing experimental, all ingredients used for preparing each blended compound were mixed in a kneader and the curing agents were subsequently incorporated on a two-roll mill. The compounds were finally shaped and vulcanized at 160ºC using compression molding before further mechanical, thermal aging and ozone resistance test as well as oil swelling resistance in different fuel types (diesel, gasohol-91 and engine oils). The results revealed that scorch and cure times, compression set, swelling ratio in diesel and engine oils of the blends tended to decrease with increasing NBR content, while cure rate index, hardness and swelling ratio in gasohol-91 increased. Of all EPDM/NBR ratios, the 70/30 EPDM/NBR blend showed the best tensile strength and tear strength. At a given blend ratio, tensile strength and tear strength of the blends before and after aging are not significantly different. This indicated that thermal resistance of the blends could be achieved at all EPDM/NBR ratios. Furthermore, when NBR was increased up to 50 %wt, the blend has good stability against ozone treatment. In summary, the development of EPDM/NBR compounds with the ratio of 70/30 %wt/wt yields the best overall properties and the raw material cost is about 13% higher than the control formula. The developed rubber formula can be used as basic knowledge for applying as the fuel tank rubber-cover product and can be further developed for other products requiring oil and heat resistance properties.